New Understandings of Teacher's Work
XII, 256 p.
Keywords: Within educational research that seeks to understand the quality and effectiveness of teachers and school, the role emotions play in educational change and school improvement has become a subject of increasing importance. In this book, scholars from around the world explore the connections between teaching, teacher education, teacher emotions, educational change and school leadership. (For this text, “teacher” encompasses pre-service teachers, in-service teachers and headteachers, or principals). New Understandings of Teacher’s Work: Emotions and Educational Change is divided into four themes: educational change; teachers and teaching; teacher education; and emotions in leadership. The chapters address the key basic and substantive issues relative to the central emotional themes of the following: teachers’ lives and careers in teaching; the role emotions play in teachers’ work; lives and leadership roles in the context of educational reform; the working conditions; the context-specific dynamics of reform work; school/teacher cultures; individual biographies that affect teachers’ emotional well-being; and the implications for the management and leadership of educationalchange, and for development, of teacher education.